Flexible learning for a large undergraduate history paper: implementation and outcomes - Roberto Rabel; Andrew Higgins (Flexible Learning Association of New Zealand, 2012)
This paper describes the conversion of a first year History paper at the University of Otago into a flexible learning paper. The work involved using distance learning techniques to generate a paper that went some way to achieving flexibility of time, place and pace of student learning.